2019
DOI: 10.3390/su11215972
|View full text |Cite
|
Sign up to set email alerts
|

Examining CEOs’ Moral Reasoning in the Automotive Industry

Abstract: This paper examines the moral reasoning trends of CEOs (chief executive officers) in the automotive industry, gauging their relations to ethical behaviors and scandals as well as analyzing the influence of scandals and other factors on their moral reasoning. For such a purpose, we carried out a moral reasoning categorization for the top 15 automotive companies in vehicle production in 2017 by applying Weber’s method to letters written by CEOs for the period 2013–2018. A positive global trend was observed, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…Geely’s CEO, yet at the conventional level, reaches stage #4, while Toyota’s CEO attains stage #6, the highest one on the moral reasoning ladder, explicitly reacting to the COVID-19. Moreover, Garcia-Ortega et al (2019) found that in front of a company scandal, CEOs neither adopted a principled level through their discourse in response, and they just tended to address more attention to stakeholders (stage #3). This is also the case of Daimler’s CEO under this exogenous crisis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Geely’s CEO, yet at the conventional level, reaches stage #4, while Toyota’s CEO attains stage #6, the highest one on the moral reasoning ladder, explicitly reacting to the COVID-19. Moreover, Garcia-Ortega et al (2019) found that in front of a company scandal, CEOs neither adopted a principled level through their discourse in response, and they just tended to address more attention to stakeholders (stage #3). This is also the case of Daimler’s CEO under this exogenous crisis.…”
Section: Resultsmentioning
confidence: 99%
“…Far from a mere introductory presentation, letters are indeed a powerful strategic communication tool for CEOs to exercise their leadership. In all, the letters of CEOs represent a valuable source to assess their moral reasoning and CSR approach (Garcia-Ortega et al, 2019; Weber, 2010).…”
Section: Literature Discussionmentioning
confidence: 99%
See 3 more Smart Citations